2022
DOI: 10.3233/shti220444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Medical Records Systems in Reporting HIV Health Data Indicators in Kenya

Abstract: Electronic Medical Records Systems (EMRs) improve the quality of patient care and reduce medical errors. Nevertheless, their role in health data indicator reporting performance is unclear. We assessed reporting completeness and timeliness of HIV indicator data to the national aggregate reporting system, District Health Information Software 2 (DHIS2) in Kenya. We compared the reporting performance of facilities with and without EMRs implementation for the year 2013 as EMRs uptake was in progress. The comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Similar results were found in a study conducted in the Brong Ahafo region in Ghana on utilising the national cluster of the District Health Information System (DHIS2) for health service decision-making at the district, subdistrict, and community levels. It was found that despite 93% of the health facilities studied submitted data to the DHIS2 platform, the evidence still suggested the low use of these data in decision-making [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in a study conducted in the Brong Ahafo region in Ghana on utilising the national cluster of the District Health Information System (DHIS2) for health service decision-making at the district, subdistrict, and community levels. It was found that despite 93% of the health facilities studied submitted data to the DHIS2 platform, the evidence still suggested the low use of these data in decision-making [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%